2020 Population Census Data Recording in Indonesia: Flexible, Effective and Efficient Software Development (Case Study: Population Recapitulation Data Recording) - Angga Fajar Sukma Alfariz (DoubleClick: Journal of Computer and Information Technology, 2021)
AbstractThe 2020 Population Census is a big agenda for the Central Statistics Agency. Implementing a Census with a very wide working area and a very large number of officers has its own challenges. The schedule of these activities was carried out when Covid-19 made the burden heavier. These challenges are not only felt in the field, but also during processing. A quick population recapitulation calculation, which is by implementing the Covid-19 protocol, demands that organizers adapt quickly. The current system is considered to have weaknesses that make processing less effective. In this study, a system was developed to assist the population census processing in the population recapitulation data recording section. This system will take advantage of various available technologies, such as Bootstrap, PostgreSQL, PHP and Codeigniter. Utilization of this technology is expected to increase effectiveness and efficiency in problem solving. The system development method applied is the Agile Model Personal eXtreme Programming Method. The system can quickly accept changes and can be adapted quickly by officers. With this system, the recording of population recapitulation data, especially in West Kalimantan Province, can run effectively.